Further Adventures of the Celestial Sleuth Using Astronomy to Solve More Mysteries in Art, History, and Literature - Olson, Donald W. (Popular Astronomy,, 2018)
From the author of "Celestial Sleuth" (2014), yet more mysteries in art, history, and literature are solved by calculating phases of the Moon, determining the positions of the planets and stars, and identifying celestial objects in paintings. In addition to helping to crack difficult cases, these studies spark our imagination and provide a better understanding of the skies. Weather archives, vintage maps, tides, historical letters and diaries, military records and the assistance of experts in related fields help with this work. For each historical event influenced by astronomy, there is a different kind of mystery to be solved. How did the changing tides affect an army's battle plans? How did the phases of the moon affect how an artist painted a landscape? Follow these exciting investigations with a master "celestial sleuth" as he tracks down the truth and helps unravel mysteries as far back as the Middle Ages and as recent as the iconic 1945 photograph of a kiss in Times Square on VJ Day. Topics or "cases" pursued were chosen for their wide public recognition and intrigue and involve artists such as Vincent van Gogh and Claude Monet; historical events such as the campaigns of Braveheart in Scotland, battles in World War II and the Korean War; and literary authors such as Chaucer, Cervantes, Shakespeare, Byron, and Edgar Allan Poe.